ANALISIS SPASIAL FAKTOR RESIKO KEJADIAN TUBERKULOSIS DI KOTA KENDARI TAHUN 2012 - , MUHAMMAD AGUSMAN SORUMBA, SKM; , Dra. Susi Iravati, Apt., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Tuberculosis or TB is still a public health problem of global challenges. In 1995, there were 9 million new TB patients and 3 million deaths from TB worldwide, and many occur in developing countries. Current conditions for infectious disease morbidity TB set 225/100.000 the number of TB cases. Data Discovery Case or Case Detection Rate (CDR) kendari city three years in a row in 2009 amounted to 50.74%, 81.71% in 2010 and amounted to 53.38% in 2011. The possibility of increasing the number of new cases is increasing every year and it is not certain that the strongest risk factor as a cause of pulmonary TB smear (+) Objective: To analyze the spatial distribution of patients with pulmonary tuberculosis smear (+) and determine the relationship of risk factors of population, environment and behavior on the incidence of pulmonary TB smear (+) Methods: The study was an observational analytic study, with cross sectional design. The number of samples of 122 respondents who comes to health care facilities and recorded utilizing poly or TB services. Research tool with structured questionnaires and GPS. The data were processed using software spatial analysis, The Moran Scatter Plot and Nearest Neighbor Hierarchical Clustering who see the distribution of relevant variables according to study regional patterns. Results: The variables that have a significant relationship with the incidence of tuberculosis in the regional pattern of poverty status, nutritional status, population density, ventilation, and lighting. There is a clustering of pulmonary TB smear (+) in Kendari city. Conclusion: There is a relationship variable density poverty status, nutritional status, housing density, ventilation, lighting and behavior. the incidence of smear-positive pulmonary TB.